(untitled) - Nelson G Hairston (Cambridge, New York, 1994)
The book gives a panaromic view of vertebrate life, classification, ecology, and behavior. In Part I, the book describes the major groups of vertebrates and their origins, and a special chapter discusses the ways in which vertebrates sense their environments. Part II covers classification and its methodology and points to the ways in which some vertebrates deviate from the routinely accepted system. Part III describes the ecology of vertebrates from two standpoints: how individuals cope with environmetal extremes, and principles of population and community ecology, as illustrated by experiments carried out in the field. Part IV describes the geographic distributions of vertebrates and considers theories of how they came to be in their current locations. Part V discusses migration and describes experiments that have elucidated the mechanisms of navigation over vast distance. Vertebrate behavior is the subject in Part VI, which deals with observations and the theories and experiments they have inspired
Keywords: vertebrates